Characterization of a Commercial PIN Diode for Stereotactic Radiosurgery Dosimetry - Matheus Fernando dos santos; Charles Nilton Do Prado Oliveira; Karen Pieri Bueno; Lucas Delbem Albino; Thiago Schmeling Fontana; Wlademir Carvalho Vasconcelos Filho; Jose Geneci da Costa Calado; Ernesto Henrique Roesler; Vinicius Saito Monteiro de Barros; Helen Jamil Khoury (Brazilian Journal of Radiation Sciences)
The stereotactic radiosurgery (SRS) is a technique that uses multiple beams extremely collimated of ionizing radiation to treat intracranial lesions and functional abnormalities, with high geometric precision and dosimetric accuracy. The use of small fields is already a reality in modern radiotherapy techniques. However, the accuracy in small-field dosimetry is challenging because of several process physics and aspects related to the detector. The aim of this paper is to evaluate the response of a dosimetric system developed by Nuclear Energy Department of Federal University of Pernambuco (DEN/UFPE) for small field dosimetry. Measurements of, output factor (OF), off-axis ratio (OAR) and percentage depth dose (PDP) were performed with this dosimetric system and compared with the results obtained with a commercial diode and treatment planning system data. The results showed that the Diode-DEN presents a reliable and economical alternative for small fields dosimetry used in treatments of SRS. This detector can be used for validation of dates obtained in commissioning of linear accelerator and inserted in Treatment Planning Systems (TPS).